2015
DOI: 10.5897/ajb2014.14180
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an efficient callus induction method from leaf and stem in kinnow mandarin (Citrus reticulata Blanco.) and citron (Citrus medica L.)

Abstract: Kinnow mandarin (Citrus reticulata Blanco.) is a highly adaptable variety among citrus cultivars in the climate of the region of Panjab, Pakistan and citron (Citrus medica L.) was the first of the citrus fruits known to become visible in the Mediterranean Basin. In Sylhet region of Bangladesh, it is commonly known as Zara lemon. The establishment of in vitro technique for seed germination and callus induction has been done for kinnow and citron in this experiment. In case of seed germination, ½ MS media supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…1A) that MS medium supplemented with 2,4-D (3.0 mg/l) recorded maximum culture establishment (97.79%) and was significantly higher as compared to all other treatments whereas, minimum culture establishment of (1.44%) was recorded on MS medium supplemented with 2,4-D (2.0 mg/l) in combination with BAP (0.25 mg/l) and NAA (1.0 mg/l). The results obtained are in line with the results of Mohammed et al (2015) [14] wherein, maximum culture establishment had been reported from leaf and stem segments of Citrus reticulata on MS medium incorporated with 2,4 D (1.0 mg/l) either alone or in combination with NAA (0.25 mg/l). Savita et al (2011b) [25] found greenish healthy callus from cotyledon explants of rough lemon on MS medium containing 2,4 D (2.0 mg/l).…”
Section: Culture Establishmentsupporting
confidence: 91%
See 1 more Smart Citation
“…1A) that MS medium supplemented with 2,4-D (3.0 mg/l) recorded maximum culture establishment (97.79%) and was significantly higher as compared to all other treatments whereas, minimum culture establishment of (1.44%) was recorded on MS medium supplemented with 2,4-D (2.0 mg/l) in combination with BAP (0.25 mg/l) and NAA (1.0 mg/l). The results obtained are in line with the results of Mohammed et al (2015) [14] wherein, maximum culture establishment had been reported from leaf and stem segments of Citrus reticulata on MS medium incorporated with 2,4 D (1.0 mg/l) either alone or in combination with NAA (0.25 mg/l). Savita et al (2011b) [25] found greenish healthy callus from cotyledon explants of rough lemon on MS medium containing 2,4 D (2.0 mg/l).…”
Section: Culture Establishmentsupporting
confidence: 91%
“…Kagzi lime and Citrus sinensis cv. Musambi; Ali and Mirza (2006) [1] in rough lemon; Mohammed et al (2015) [14] in Citrus reticulata and Kaur (2018) [9] in rough lemon. Kaur (2018) [9] reported efficient protocol for in vitro embryogenic callus induction of rough lemon with 2, 4-D (1.0 mg/litre) in combination with BAP (1.0 mg/litre) produced early and highest percentage of callus with formation of somatic embryos.…”
Section: Callus Inductionmentioning
confidence: 98%